The objective of islamic economic and islamic banking in light of maqasid al-shari’ah - Mustafa Omar, Mohammed; Syahidawati , Shahwan (IDOSI Publications, 2013)
There has been variation in the objectives of Islamic economics. It is also assumed that the objectives of Islamic economics are supposed to guide the objective of Islamic banking and Finance. Over the years, there seem to be widening gap between the two Islamic disciplines in terms of their objectives. There are hardly any studies that have formally documented the issues that have contributed to the widening gap between the two disciplines and whether these differences are reconcilable. This paper therefore is a critical survey of the literature on the subject, using Maqasid al-Shari’ah as a benchmark for examining the variations and relationship between both disciplines. The issues of theories versus practice was given due emphasis. The study, which is exploratory in nature, adopted content analysis and inductive method to achieve its objectives aforementioned. The study has concluded from the observation of the selected literatures that the five elements of Maqasid al-Shari’ah were fully observed in the objectives of Islamic economics and Islamic bank. However, it is also found that the objectives of Islamic banks mostly aimed towards profit-oriented entity rather than social-based entity. Thus, it is suggested that Islamic banks’ objectives should promote the objectives of Islamic economics thus inculcating as well Maqasid al-Shari’ah in its holistic direction.